PROFESSIONAL PREFERENCES OF YOUNG PEOPLE AS AN INDICATOR OF SOCIAL CHANGES - Galina I. Saganenko; Alexandra A. Stepantsova; Elena I. Stepanova (Высшее образование в России)
The article is devoted to studying of changes in professional preferences of graduates of schools in several points of time. In 1965 there was held an original empirical research of Leningrad sociologist Vera Vodzinskaya. 30 years later, in 199481995, the diploma projects on the basis of surveys of graduates of 5 schools of St. Petersburg were carried out. As in the first basic research there was used a list format (from 55 to 60 units) professions, a set of estimation criteria (from 5 to 8), a scale with 1810 points. In 50 years, in 2014, the diploma project of Aleksandra Stepantsova was realized (58 professions, 8 criteria, and a 108points scale). Research studies were carried out by graduates - sociologists of S.8Petersburg State University of Culture and Arts. When preparing a format of survey every time it was necessary to solve two main problems: (1) which professions to include into a list for estimation (because one part of professions disappeared, others appeared, and also it was necessary to keep a part of professions as a base for comparison) and (2) what criteria to use for estimating professions (it was required to fill up the list of criteria in order to specify essential details of a situation with professional representations of modern graduates of schools). There is also one more serious limiter exists - the volume of the task offered to school students (it is possible to use only two lessons for the survey - 90 minutes). The aim of this article is to represent the results of research82014 in a comparative context with other researches, to mark emphases on the changes revealed.